ISLAMIC COMMUNICATION SKILLS IN ADOLESCENT COUNSELING: A THEORETICAL REVIEW OF THE CHALLENGES OF THE ERA OF MORAL DISRUPTION - Heri Kurniawan; Hidayati, Sri (As-Sulthan Journal of Education, 2025)
The development of digital technology in the era of disruption has presented complex moral challenges for Muslim youth. Phenomena such as identity crisis, value disorientation, and increasing deviant behavior arise due to the rapid flow of global culture and exposure to social media that has little spiritual value. This paper aims to theoretically examine Islamic communication skills in adolescent counseling practice in response to these challenges. This research uses a qualitative-descriptive approach with a library research method through the analysis of the latest scientific books and journals. The study focuses on elements of Islamic communication such as empathy, rahmah (compassion), active listening, tabayyun (clarification), and reflective communication based on the values of muhasabah and tazkiyatun nafs. The results of the study showed that Islamic communication skills are not only able to build a supportive relationship between counselors and counselors, but also strengthen the spiritual, emotional, and moral aspects of adolescents. The Islamic communication model offered is transformative, relational, and value-based, and can be effectively implemented in educational settings such as schools and Islamic boarding schools. This model is a strategic alternative in efforts to build character and mentor adolescents during an increasingly real value crisis.